Salt gradient-driven adaptation in okra: uncovering mechanisms of tolerance and growth regulation - Yang, Xi; He, Jiuxing; Xu, Lifeng; Kong, Meng; Huo, Qiuyan; Song, Jiqing; Han, Wei; Lv, Guohua (Frontiers in Plant Science, 2025)
Soil salinity is an increasingly critical constraint on crop establishment and yield stability, especially in marginal and irrigated agricultural zones. Despite its nutritional and economic value, the mechanistic basis of salt tolerance in Abelmoschus esculentus (okra) remains poorly defined. Here, we integrated physiological phenotyping with transcriptome profiling to elucidate the stage-specific strategies employed by okra in response to NaCl stress. Our results revealed a bifurcated salt response: germination was highly sensitive, with complete inhibition at ≥ 0.5% NaCl, whereas seedling growth exhibited a hormetic pattern, being promoted under mild salinity (0.1–0.3%) and suppressed at higher levels. Photosynthetic integrity and photoprotection were preserved under low salinity but declined under severe stress, accompanied by increased oxidative burden. Transcriptomic analyses revealed that moderate salt stress elicited the coordinated activation of ion homeostasis genes, calcium signaling components, and GH3-family auxin-responsive genes (log2FC = 2.3–2.5), suggesting a critical role for dynamic auxin conjugation in growth maintenance under ionic stress. Concurrently, ROS detoxification, cytoskeletal remodeling, and metabolic adjustments were induced to support cellular stability. These findings defines okra’s salt tolerance threshold, reveals key molecular targets for genetic improvement, and provides a scientific foundation for the sustainable deployment of salt-tolerant okra in saline agriculture and land reclamation.